2020
DOI: 10.1097/cce.0000000000000278
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Modules to Enhance Informed Consent in the ICU: A Pilot Study

Abstract: Objectives: Obtaining informed consent for commonly performed ICU procedures is often compromised by variability in communication styles and inadequate verbal descriptions of anatomic concepts. The objective of this study was to evaluate the efficacy of an audiovisual module in improving the baseline knowledge of ICU procedures among patients and their caregivers. Design: Prospective, observational study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…On the other hand, participants in the written consent group had better understanding on one measure of study procedure. This differs from previous studies that found virtual multimedia informed consent had better understanding of use of their personal health information (PHI) and how to withdraw from the study, compared to their traditional paper consent counterparts [7,[17][18]. Our findings suggest that different formats may communicate different aspects of study information more effectively, and perhaps both video and written consent forms should be available to study participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, participants in the written consent group had better understanding on one measure of study procedure. This differs from previous studies that found virtual multimedia informed consent had better understanding of use of their personal health information (PHI) and how to withdraw from the study, compared to their traditional paper consent counterparts [7,[17][18]. Our findings suggest that different formats may communicate different aspects of study information more effectively, and perhaps both video and written consent forms should be available to study participants.…”
Section: Discussioncontrasting
confidence: 99%
“…We conducted an online experiment with 435 adolescents and young adults (aged [13][14][15][16][17][18][19][20][21][22][23][24] recruited by an online survey research provider. Each participant was randomly assigned to view either a short-form video consent or a written consent form describing a behavioral study of a social media-based vaping cessation program.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, audiovisual resources have been shown to improve informed decisions about cardiopulmonary resuscitation 12 and ICU procedures. 13 Affective Responses to Bodily Imagery Although visual information can be helpful in decision making, how this visual information is provided has ethical relevance because of the salience and affective impact of such information. Bodily imagery, in particular, has been employed to discourage various health-related choices, including by placing warnings in the form of images of rotting teeth and blackened lungs on cigarette packages to decrease smoking 14 and requiring the viewing of fetal ultrasound images with the intent of reducing abortions.…”
Section: Commentarymentioning
confidence: 99%
“…Although visual imagery can activate emotion-driven decision making, visual imagery is not, as we have said, necessarily incompatible with good decision making. 12,13 Yet, in many cases, the control that the clinician exercises over how or when the body is shown is manipulative because a patient's body is used as a means to the clinician's preferred decisional outcome. In Ms K's case, the clinical team believed her best interests were disregarded by her surrogates.…”
Section: Commentarymentioning
confidence: 99%